2016
DOI: 10.1186/s13013-016-0071-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of adolescents conservatively treated for idiopathic scoliosis in Korea: a cross-sectional study

Abstract: BackgroundYoung adolescents with scoliosis are more likely than adults to experience psychological distress affecting health-related quality of life (HRQoL). Adolescence is a sensitive period of psychological development, and thus physical deformity from scoliosis can negatively affect body image and appearance of adolescents. The present study evaluated HRQoL in young Korean adolescents with idiopathic scoliosis and identified related factors.MethodsOne hundred and ten adolescents with idiopathic scoliosis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…Idiopathic scoliosis had the prevalence of about 0.4% to 7% amongst adolescents in Asian countries 1 - 12 . In patients with idiopathic scoliosis, earlier detection and diagnosis allows early conservative treatment, which is bracing and this can avoid unnecessary surgery and preserve a higher health-related quality of life scores 13 , 14 . Late detection may lead to higher rates of patient needing surgery and if this condition is left untreated, it can progress to severe scoliosis, which has been shown to affect pulmonary function of patients 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic scoliosis had the prevalence of about 0.4% to 7% amongst adolescents in Asian countries 1 - 12 . In patients with idiopathic scoliosis, earlier detection and diagnosis allows early conservative treatment, which is bracing and this can avoid unnecessary surgery and preserve a higher health-related quality of life scores 13 , 14 . Late detection may lead to higher rates of patient needing surgery and if this condition is left untreated, it can progress to severe scoliosis, which has been shown to affect pulmonary function of patients 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding function, it is important to infer that the physical problem, the pain, and, in more advanced cases, the impairment of pulmonary and cardiac activity are relevant factors that hinder the participation of these individuals in social and physical activities, limiting their daily activities. 2 On the other hand, another study 4 with a similar objective, reported that there was no significant change in relation to the activity/function domain, observing that the study population had a good perception of their activities.…”
Section: Discussionmentioning
confidence: 95%
“…Referring to the results in the mental health domain, we observed conformity with most of the articles published about the quality of life in patients with scoliosis, there being great concern in this area, since they present feelings that range from unhealthy thoughts to more severe symptoms, such as suicidal thinking. 2,4 However, it is noted that the regular practice of physical activity is a factor for a better state of mental health, resulting in a better quality of life. 12 In addition to improving physical and mental well-being, physical exercises improve the mobility, flexibility, strength, and balance of Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the magnitude of the Cobb angle, has shown to be associated with quality of life where a larger curve had a negative impact (73). On the contrary, other studies have shown no correlation of the curve size and quality of life (69,74). Furthermore, onset of idiopathic scoliosis (i.e.…”
Section: Surgerymentioning
confidence: 99%